Meaning of Life in Institutionalized Older Adults from the Humanist-Existential Approach - Molina Codecido, Cesar (2021)
Objective. Identify the meaning of life in a group of institutionalized older adults, from a humanistic-existential perspective. Method. A phenomenological qualitative design was carried out where eight older adults aged between 74 and 99 years were interviewed, using the life story technique, carrying out a thematic narrative analysis. Results. Three thematic axes were observed (activities prior to the institution, history of personal life, and vital events around suffering). From these, the existential values that allowed to give an account of a meaning of life in institutionalized older adults emerged. In conclusion, older adults orient their life towards themselves, towards other people within the institution, and have a meaning of death.